Desenvolvimento de blendas poliméricas de PLA/Amido e PVDF/Amido para aplicações como biomateriais - Pereira, João Domingos Augusto dos Santos [UNESP] (2016)
Foams of PLA/Starch and PLA/Starch/Sepiolite (SEP) with different compositions were produced. The following techniques were used in the samples characterization: i) scanning electron microscopy (SEM); ii) density (ρ) measures; iii) differential scanning calorimetry (DSC), iv) mechanical analysis (flexion and traction); v) dynamic mechanical thermal analysis (DMTA); vi) in vivo test. In the SEM images, in both foams and precursors, the interface between the phases was eminently physic with two distinct phases with gaps between them, and an increase in size of the gaps was observed in the foam. It was observed that in the samples with SEP occurred greater generation of smaller cell and more compact. This demonstrates that SEP presented, as well as the starch granules, the nucleating agent behavior. In ρ measures the lowest values were found in samples originating from the autoclave and glycerine bath, respectively. These decreases were consistent with the expansion of PLA matrix observed in the SEM images. In the DSC measurements in general, the starch addition to PLA resulted in increased Xc. This effect happened because the interface between starch and PLA be more energetic, which facilitated the crystals formation in the PLA matrix. In composites containing SEP, generally larger Xc values were observed when compared with the PLA/starch blends in the same proportions materials. This behavior is probably related to the effect of the SEP as a nucleating agent in the PLA. In the mechanical analysis, flexion and traction, with increasing starch content in the blends lower resistance and maximum deformation as the tension and rupture deformation were obtained. Additionally, the same decrease in performance was maintained for composites SEP. However, in the tensile test, these samples showed values greater than the blends. In the results observed via DMTA, in general, the addition of starch and SEP resulted in a stiffness decrease of PLA matrix, that is, E' lower values for blends and composites when compared with pure PLA samples. In the in vivo study, approved by the Ethics Committee on Animal Use the FCT/UNESP, Presidente Prudente, São Paulo, Brazil (process No. 02/2014), 18 rats Wistar (Rattus norvegicus, albino variety, Rodentia, Mammalia) were used with age of 120 days, obtained from the Universidade do Oeste Paulista (UNOESTE). The animals underwent surgical procedure for samples implantation, after 40 weeks counted from the implantation surgery date, the samples were removed. For structural analysis of removed samples and tissues SEM morphology measurements and optical microscopy (OM) were performed respectively. It was observed by SEM technique that the surfaces of post-implant samples showed a pattern coating by biological tissue with capsular morphology. In the photomicrographs obtained by OM, structures such as muscle fibers; adipose tissue (AT) and dense connective (TDC) were observed. Furthermore, in photomicrographs were observed in some few focal inflammatory infiltrate. Next to the muscle tissue was observed the presence of AT permeated by the TDC, featuring as capsular tissue.